ESCALA PARA AVALIAÇÃO DAS ATITUDES DO ENFERMEIRO NO CUIDADO ÀS FAMÍLIAS NA ATENÇÃO PRIMÁRIA À SAÚDE. - BRAGA, Lorena Carvalho (2019)
The nurses have the ethical and moral commitment to involve the families on their health care, considering that Family has a meaningful impact on health and the welfare of each member. The Centered Care on Family means that families represent a constant in the life of the members and when they envolve the Family in the care, the nursing will provide and prefer cares of excellence. The nurse’s attitudes are decisions for the quality of the established relations with Family and for the therapeutic process in the context of Primary Attention to Health. Therefore, it is necessary identify the nurses attitudes by a valid and reliable scale which points for a changing way and care improvement to the families. This search has as goals: Make a scale to predict the nurse’s attitudes in the assistance with families in the context of Primary Attention to Health and validate content the Scale Nurse attitudes in the Assistance with families in the Primary Attention to Health. It is a methodological search, quantitative kind. To construct the scale it was considered assumptions of the Centered Care on Family and the items of the Scale The Importance of Families in the Nursing Cares – Nurses Attitudes. It was used the Delphi technical as a procedure method for the scale validation. The content judges who participated from the evaluation, they are masters and doctors nurses with expertise in Family Nursing, identified by the Lattes Platform. The data collect occurred between July of 2018 and January of 2019 by two evaluation rounds sent by Google Docs®, with 14 and 8 nurses on the first and second rounds, respectively. The judges used a categorical scale of four points to judge the criteria. The answer concordance was evaluated by the Content Validity Index and by the concordance rate, whose values were: 0,88 and 88% on the first round and 0,94 and 94,8% on the second round. To analyze the intensity degree of concordance among judges about the criteria evaluation, they were using the Kappa Index which showed a weak concordance, tolerable and regular on the first round, evolving for a good and great concordance. To the end of the evaluations, the Nurse Attitudes Scale in the assistance to Families in the Primary Attention to Health was made presenting with 31 distributes items in four dimensions: Family as the assistance focus; partnership and co-responsibility attitude; support to the Family and reception to this Family. The validation and construction for an instrument that proposes measure its goal, encouraging to an implantation effective in its caring processes. The nurses daily Interact with families, however, it is necessary go beyond, examining attitudes and practices to take care of a Family.